Holographic interferometry as a method to detect welding failures on ribbed iron structures - Vincitorio, Fabio Miguel (2013)
Metallic structures made of ribbed iron bars (ADN-420) are of common use in sheds and supporting structures. Usually, trusses are constructed with many pieces of ribbed iron bars, combined together through a welding process. Although ribbed iron manufacturers do not recommend this type of structure it is still frequently used. The main weakness of these trusses is the welding point because ribbed iron is not a material suitable for welding. This work presents results obtained from an analysis of welding points between ribbed iron bars extracted from a collapsed truss, by means of conventional (optical) and digital holographic interferometry (HI and DHI, respectively). The experiments were divided in two different series of studies. The first series were performed by HI on metallographic samples while the second series were done by DHI on different welding points. These results were complemented by metallographic analysis made in an external laboratory. DHI indicated that the bars did not have important failures but evidenced defects in one of the welding points under analysis. This information together with metallographic results allowed inferring that the collapse was probably due to an error in the design of the structure, since the iron bars were out of standard compliance.